Biological aspects of Ocyptamus gastrostactus and biological controller Pachyneuron albutius, in Panama - Santos Murgas, Alonso (2024)
In the present work, information is provided on biological and ecological aspects of the fl y Ocyptamus gastrostactus (Wiedemann, 1830) (Diptera: Syrphidae) and its larvae are recorded carrying out predation on aphids, Sarucallis kahawaluokalani (Kirkaldy, 1906) (Insecta: Hemiptera: Aphididae) on plants from Lagerstroemia indica (L.) Pers. (Ly thraceae: Myrtales). Also, parasitism of the pupae of the fl y O. gastrostactus by the parasitoid wasp Pachyneuron albutius Walker, 1843 (Hymenoptera: Pteromalidae) in the fi eld is recorded for the fi rst time. Distribution information is provided for all the species involved in the work.